TAX EXCHANGE OF INFORMATION AND INTERNATIONAL COOPERATION IN BRAZIL - Heloisa Estellita; Frederico Silva Bastos (Revista Direito GV)
Globalization and internationalization of companies are phenomena that need to be considered by modern tax administrations. In many situations, such as tax evasion, harmful tax competition and money laundering, domestic statutes seem to be ineffectual in a global dimension. Fo cope with that, new forms of regulation and regulators emerge. Under this view, an effort towards signing international treaties, conventions and agreements seems to be a feasible solution. The brazilian legal framework contains principles and rules that make international cooperation and exchange of information (eoi) with other countries possible. Furthermore, the brazilian tax administration has wide-ranging access powers to obtain information for international exchange purposes and has the tools to coercively produce such information. Brazil is following the right path to implement international exchange of information standards. However, there are some obstacles that need to be fixed for a more efficient implementation of these mechanisms. This article examines some topics of the brazilian legal and institutional framework on the tax exchange of information, such as a new model of approach of the tax administration, the tax transparency agenda and the international agreements on eoi matters, the brazilian supreme court rulings under bank secrecy and the rights of brazilian taxpayers regarding eoi.